Red pericarp introgression lines derived from interspecific crosses of rice: physicochemical characteristics, antioxidative properties and phenolic content. (3rd April 2014) - Sharma, Neerja; Kaur, Rimaljeet; Mangat, Gurjit S; Singh, Kuldeep
Abstract BACKGROUND Antioxidative properties and physicochemical characteristics of introgression lines (ILs) and their recurrent parents were analyzed. In addition, catalase (CAT) and superoxide dismutase (SOD) activities and free radical‐scavenging capacity were evaluated, since these are important antioxidative properties for developing nutraceutical and functional foods. RESULTS Comparative analysis of the brown and milled rice fractions of ILs with their respective recurrent parents revealed 2.26‐ and 1.22‐fold increase in total phenolics, 1.95‐ and 2.09‐fold increase in flavonoids, 8.38‐ and 6.80‐fold increase in proanthocyanidins and 1.55‐ and 1.20‐fold increase in tannins in brown and milled rice fractions respectively. Higher CAT (1.36‐ and 1.89‐fold) and SOD (1.71‐ and 2.02‐fold) activities and Trolox equivalent antioxidant capacity (TEAC, 7.13‐ and 1.98‐fold) were observed in brown and milled rice fractions respectively of ILs compared with their respective recurrent parents. A high and positive correlation was obtained between TEAC and total phenols (0.73, P ≤ 0.01), flavonoids (0.66, P ≤ 0.05) and proanthocyanidins (0.69, P ≤ 0.05). The yield parameters and physicochemical characteristics of the grains, in general, were comparable in the ILs and their respective recurrent parents. CONCLUSION The ILs of rice reported in the present study exhibited significant positive differences in the content of phenolic constituents and antioxidant properties with good grain quality characteristics over their recurrent parents, indicating their potential as a natural source of phytochemicals for nutraceutical and functional food development. © 2014 Society of Chemical Industry